2023
DOI: 10.3390/ijms24065157
|View full text |Cite
|
Sign up to set email alerts
|

Anoxia Rapidly Induces Changes in Expression of a Large and Diverse Set of Genes in Endothelial Cells

Abstract: Sinusoidal endothelial cells are the predominant vascular surface of the bone marrow and constitute the functional hematopoietic niche where hematopoietic stem and progenitor cells receive cues for self-renewal, survival, and differentiation. In the bone marrow hematopoietic niche, the oxygen tension is usually very low, and this condition affects stem and progenitor cell proliferation and differentiation and other important functions of this region. Here, we have investigated in vitro the response of endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In previous studies conducted by our group with HUVEC maintained in anoxia (<1% O 2 ), transcriptomic analysis revealed that among the dysregulated genes during the O 2 deprivation, particularly Hypoxia‐inducible factor 1α ( HIF ‐ 1α ) and HIF‐1α‐dependent angiogenic factors like the vascular endothelial growth factor (VEGF) emerged 47 . Therefore, RT‐PCR was used to determine the gene expression of HIF ‐ 1α , VEGF , and the Thioredoxins ( TRX ‐ 1 and 2 ), in hypoxic vs normoxic cells (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies conducted by our group with HUVEC maintained in anoxia (<1% O 2 ), transcriptomic analysis revealed that among the dysregulated genes during the O 2 deprivation, particularly Hypoxia‐inducible factor 1α ( HIF ‐ 1α ) and HIF‐1α‐dependent angiogenic factors like the vascular endothelial growth factor (VEGF) emerged 47 . Therefore, RT‐PCR was used to determine the gene expression of HIF ‐ 1α , VEGF , and the Thioredoxins ( TRX ‐ 1 and 2 ), in hypoxic vs normoxic cells (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies conducted by our group with HUVEC maintained in anoxia (<1% O 2 ), transcriptomic analysis revealed that among the dysregulated genes during the O 2 deprivation, particularly Hypoxia-inducible factor 1α (HIF-1α) and HIF-1α-dependent angiogenic factors like the vascular endothelial growth factor (VEGF) emerged. 47 Therefore, RT-PCR was used to determine the gene expression of HIF-1α, VEGF, and the Thioredoxins (TRX-1 and 2), in hypoxic vs normoxic cells (Figure 5). The downregulated metabolites are shown in green, the upregulated ones in red, the not detectable ones in gray, and those that do not statistically change (considering normoxia vs. hypoxia and treated group vs. hypoxia) in black.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Thus, understanding the players governing the response of ECs in inflammatory states is crucial to develop aids to maintain endothelial homeostasis and the prevention of vascular diseases. Very recently, we also demonstrated that SIRT6 may prevent oxidative stress damages via the upregulation of NADPH to counteract reactive oxygen species in HUVECs [ 52 ]. Altogether, our results suggest that SIRT6 activation through pharmacological approaches may represent a useful strategy to (a) counteract endothelial inflammatory responses and (b) sustain the production of platelets.…”
Section: Discussionmentioning
confidence: 99%